An unprecedented Ni14SiW9 hybrid polyoxometalate with high photocatalytic hydrogen evolution activity. Issue 29 (20th March 2019) - Paille, Grégoire; Boulmier, Amandine; Bensaid, Alexandre; Ha-Thi, Minh-Huong; Tran, Thu-Trang; Pino, Thomas; Marrot, Jérôme; Rivière, Eric; Hendon, Christopher H.; Oms, Olivier; Gomez-Mingot, Maria; Fontecave, Marc; et al.
Abstract : A unique polyoxometalate with 14 nickel and 9 tungsten ions catalyses the reduction of protons under visible light. Abstract : A unique polyoxometalate complex made up of a tetradecanuclear nickel bisphosphonate cluster capping a SiW9 unit has been characterized. This stable compound exhibits a high hydrogen evolution reaction photocatalytic activity under visible light irradiation via a reductive quenching mechanism.